Characterization of peanut (Arachis hypogaea) bandi - Seguera, Charisse Marie Occeña
Characterization of peanut bandi using muscovado sugar, refined sugar and washed sugar by means of proximate composition, physico-chemical analyses and sensorial evaluation was assessed.